Financial Soundness Indicators Compilation Guide 2019. (Manuals and Guides, 2019)
The 2019 Financial Soundness Indicators Compilation Guide (2019 Guide) includes new indicators to expand the coverage of the financial sector, including other financial intermediaries, money market funds, insurance corporations, pension funds, nonfinancial corporations, and households. In all, the 2019 Guide recommends the compilation of 50 FSIs-13 of them new. Additions such as new capital, liquidity and asset quality metrics, and concentration and distribution measures will serve to enhance the forward-looking aspect of FSIs and contribute to increase policy focus on stability of the financial system.